1998
DOI: 10.1111/j.1469-7793.1998.599bb.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transcranial magnetic stimulation on the soleus H reflex during human walking

Abstract: The effect of transcranial magnetic stimulation (TMS) on the soleus H reflex was investigated in the stance phase of walking in seventeen human subjects. For comparison, measurements were also made during quiet standing, matched tonic plantar flexion and matched dynamic plantar flexion. During walking and dynamic plantar flexion subliminal (0.95 times threshold for a motor response in the soleus muscle) TMS evoked a large short‐latency facilitation (onset at conditioning‐test interval: −5 to −1 ms) of the H re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
121
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(136 citation statements)
references
References 43 publications
10
121
5
Order By: Relevance
“…In all likelihood, there are other systems that may modulate the corticospinal transmission at the level of the corticospinal terminals, although at present, we have no knowledge of such systems. Nevertheless, because our findings are essentially similar to those obtained by Petersen et al (1998), we believe that increased cortical excitability is the most likely explanation of the larger short-latency facilitation in the early part of downstroke during bicycling.…”
Section: Evidence For Increased Corticospinal Transmission In Early Dsupporting
confidence: 75%
See 2 more Smart Citations
“…In all likelihood, there are other systems that may modulate the corticospinal transmission at the level of the corticospinal terminals, although at present, we have no knowledge of such systems. Nevertheless, because our findings are essentially similar to those obtained by Petersen et al (1998), we believe that increased cortical excitability is the most likely explanation of the larger short-latency facilitation in the early part of downstroke during bicycling.…”
Section: Evidence For Increased Corticospinal Transmission In Early Dsupporting
confidence: 75%
“…In previous studies (Nielsen and Petersen 1995;Petersen et al 1998; see also Baldissera et al 1993;Mazzocchio et al 1994), it has been argued that the shortlatency facilitation of the H reflex produced by TMS reflects transmission in the fast conducting monosynaptic pathway to the spinal motoneurons. As argued by , it is unlikely that any other pathway influences the size of the facilitation within the initial 0.5-1.0 ms after its onset.…”
Section: Evidence For Increased Corticospinal Transmission In Early Dmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in human infants, the difficulty of evoking motor responses through electrical stimulation of the rostral PrG does not seem consistent with the existence of early mature descending projections (15,16). Also, in adults, transcranial magnetic stimulation studies have suggested, in apparent contrast with monkey data, that late-maturing corticomotoneural cells are present in the human rostral PrG (17,18).…”
mentioning
confidence: 48%
“…However, at comfortable speed, vestibulospinal control is less than during slow or fast speed (Hirasaki et al 1999;Jahn et al 2000). Given the powerful cortical control of ankle muscles during walking (Petersen et al 1998(Petersen et al , 2001, it might be possible that the activation of midbrain structures by primary motor cortex contributes to the depression of group II crossed action. Alternatively, the depression occurred when the opposite leg was in the swing phase and soleus was stretched.…”
Section: Possible Mechanisms and Functional Implicationsmentioning
confidence: 99%